Skin toxicity in BRAF(V600) mutated metastatic cutaneous melanoma patients treated with vemurafenib - Nowara, Elzbieta; Huszno, Joanna; Slomian, Grzegorz; Nieckula, Jaroslaw (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction: The use of orally available BRAF kinase inhibitor – vemurafenib is associated with numerous adverse skin reactions. Aim: To assess the safety and early side effects of vemurafenib treatment in the unselected group of patients treated at the outpatient clinic, in particular the assessment of the incidence of skin cancer. Material and methods: We carried out a systematic study of patients (pts) treated with vemurafenib. Skin toxicity during vemurafenib therapy was analyzed. Toxicity was determined on the basis of the toxicity scale CTCAE, version 4.0. Results : The most common cutaneous side effects were hyperkeratotic perifollicular rash (69%) and photosensitivity (15%). Skin rash developed more frequently in the first month of treatment. Squamous cell carcinoma occurred in 38% of patients. Patients with skin cancer development during vemurafenib therapy had non-significantly longer overall survival (OS) than patients without skin cancer, p = 0.4. Skin cancer developed more often in women than in men (60% vs. 25%), p = 0.249. It was detected only in patients with normal weight compared to overweight patients (55% vs. 0), p = 0.09. The median OS was 26 months and median OS from the time of distant metastases diagnosis was 9.8 months. In patients with a low body mass index, shorter OS was observed, p = 0.09. Conclusions : The incidence of squamous cell carcinoma was high (38%). This study has many limitations mostly due to a small group of patients. That is why the results should be taken into consideration with caution. The proper symptomatic treatment in cooperation with dermatologists allows to continue the vemurafenib therapy.